Educational Media in the Perspective of the Qur'an and Al-Hadith - Ruhyan; Lukman Hakim (PT ARRUS Intelektual Indonesia, 2024)
This study endeavors to delineate the utilization of media through the lens of Islamic teachings. Within the realm of academia, educators are mandated to adeptly employ instructional materials that are in accordance with contemporary standards and tailored to students' needs. Employing the descriptive approach, this scholarly article expounds on the correlation between pedagogical media theory and the utilization of media as elucidated in the Qur'an and Hadith. Through critical analysis, numerous verses from the Qur'an and sayings of the Prophet Muhammad were discovered to resonate with modern theories regarding the integration of various forms of media, ranging from audio and visual aids to technology-driven multimedia platforms, in educational settings. It is envisaged that upon perusing this publication, educators will gain insights into the significance of media incorporation from an Islamic perspective, recognizing that the strategic use of media can significantly enhance the attainment of educational objectives.